ANALISIS YURIDIS PERAN NOTARIS DALAM PEMBUATAN AKTA PENDIRIAN PERSEROAN TERBATAS PENANAMAN MODAL ASING (STUDI PENELITIAN KANTOR NOTARIS DEBORA EKAWATI LUKMAN DADALI, KOTA BATAM) - Hendri Tri Sutrisno; Lagat Parroha Patar Siandari; Siti Nurkhotijah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Foreign Investment in Indonesia is one of the most important supporting factors for the progrerss of the country’s economy. Foreign investors who will do business in Indonesia required to establish a limited laiability company. A Notary official authorities made the deed of establishment limited liability company. This study attemps to analyze a legal arrangement, the implementation of, factors, obstacles and a solution about the the role of the notary in made the deed of establishment of limited liability company foreign capital invesment (PT PMA). This study yuridis empiris by digging use of information obtained from the interviews and data from a study literature. The research uses normative juridical approach to update the data secondary and sociological juridical approach to update the data primary. This research result indicates that, the notary in authority made the deed of establishment of the company limited foreign capital investment regulated in the law of number 12 years 2014 on changes to the law number 30 years 2004 about office of the notary who become a legal basis for the a notary.Keywords : Notary, Deed, Foreign Investment.